CALCULATION MODEL AND EXPERIMENTAL STUDY ON SEDIMENT EROSION OF SLOPE UNDER EXTERNAL-SOIL SPRAY SEEDING - Can Li; Haiqing Zhou; Qianghui Song; Yang Liu; Yixin He (Civil Engineering Journal, 2019)
Due to the current lack of theoretical study on rain erosion of the slope under external-soil spray seeding, the calculation model applicable to slope sediment erosion under external-soil spray seeding was derived from hydraulics theory and energy method. Designed slope scouring test on indoor model, conducted 3 separate scouring tests under 3 different slope rates (1:0.75, 1:1, 1:1.25) and 3 different rainfall intensities (120, 150, 180mm/h). The rationality of the calculation model was verified by the experimental data. Meanwhile, also analysed the developing regularities of slope erosion and relationship among sediment erosion, rainfall duration, rainfall intensity and slope rate. The results show that the relative error between the theoretical value and measured data is within 18%, and the calculation model can accurately predict the sediment erosion of the slope under external-soil spray seeding to some extent; the slope under external-soil spray seeding is lack of erosion resistant ability, and the slope erosion is mainly rill erosion and layered surface erosion; the amount of sediment erosion is positively correlated with rainfall intensity and slope rate. The relationship between growth rate and rainfall duration basically remained the same during the first 20 minutes, and then gradually decreased.